Suicide in Chinese Graduate Students: A Review From 2000 to 2019 - Cheng, Yun; Zhang, Xiao Meng; Ye, Shui Ying; Jin, Hui Min; Yang, Xiu Hong (Frontiers in Psychiatry, 2020)
Suicide is an important public problem in China. The characteristics of Chinese graduate students’ suicides and the reasons they occur have never been reported systematically. We conducted a systematic search of public reports on local media and medical websites in this review to gain a basic understanding of these questions. A total of 150 cases of graduate students’ suicides were reported from 2000 to 2019. Among the 150 students, 65.8% were male, nearly half between 26–30 years old, most (83.3%) never married, and 43.4% of graduation students committed suicide in graduation year and postponed years. Top three suicide methods were jumping, hanging, and drowning. Graduation pressure, depression and academic pressure were the three leading suicidal causes. There is an urgent need for the Chinese government and universities to pay more attention to prevent suicides among graduate students.